-: - - Li, Kang; Yu, Yanqiu; Liu, Xiaojing (Journal of Medical Biochemistry, 2025)
Objective: This study aimed to evaluate the therapeutic effects of glucocorticoids (GCs) combined with tacrolimus (TAC) in the treatment of Neural Epidermal Growth Factor-Like 1 (NELL1)-positive idiopathic membranous nephropathy (IMN), with a focus on clinical outcomes, nutritional status, and inflammatory response.Methods: A total of 84 NELL1-positive IMN patients from Cangzhou Central Hospital (January 2020 – February 2024) were randomly assigned to a research group (GCs + TAC) and a control group (GCs alone). The research group received methylprednisolone (0.5g), prednisone (0.5 mg/kg), and tacrolimus (0.05 mg/kg/day), while the control group was treated with methylprednisolone and prednisone alone. Clinical parameters, including renal function, blood glucose, lipids, nutritional proteins, and cytokine levels (IL-6, IL-10, IL-2, IL-17), were measured at baseline and after six months of treatment. Nutritional status was assessed using the Nutritional Risk Screening 2002 (NRS 2002).Results: There were no significant differences in clinical efficacy or adverse reactions between the two groups. However, the research group exhibited significant improvements in renal function, glycemic control, lipid profile, and nutritional status (P < 0.05). Furthermore, the research group showed a more favorable cytokine profile, with greater reductions in pro-inflammatory cytokines (IL-6, IL-17) and increases in anti-inflammatory cytokines (IL-10, IL-2) compared to the control group (P < 0.05). Both groups had comparable safety profiles, with no significant increase in adverse events.Conclusion: The combination of GCs and TAC is an effective and safe therapeutic option for NELL1-positive IMN, improving clinical outcomes, maintaining nutritional stability, and modulating immune responses without increasing adverse reactions.